Perception of Preparers and Auditors on New Revenue Recognition Standard (IFRS 15): Evidence From Egypt - Amr M. Khamis (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
In May 2014, the International Accounting Standards Board (IASB) and the Financial Accounting Standards Board (FASB) issued long-awaited converged standard on revenue recognition, IFRS 15 and ASU 2014-09 (Topic 606) Revenue from Contracts with Customers, that sets out the principles for when revenue should be recognized and how it should be measured, together with related disclosures and will replace the all current revenue standards in IFRS and US.GAAP. Although the actual implementation is still in the future, now is the time for all preparers, auditors and users of financial statement to understanding of the new recognition and disclosure requirements and prepare to implement them, because the new provisions of IFRS 15 will impact in all entities in all industries, but the extent of the impact can vary significantly. This paper test the perception of Egyptian preparers and auditors on IFRS 15, we focus on the level of familiarity, standard clarity and ease of application across different business sectors in Egypt. The final sample of the study consisted of 31 auditors and 34 preparers (which consist of chief accountants, account executives and etc.), a majority of the participants (88.3%) were from local accounting firms or Listed companies operating in various business sectors. Both the auditors and preparers are experienced accountants with mean years of experience of 7.6 and 8.56 years respectively. We find that generally Egyptian accountants and auditors surveyed are still not ready to adopt and did not have sufficient knowledge about IFRS15, as well as, they afraid of the new revenue recognition requirement (which increased discretion and professional judgment in revenue recognition) and its potential impact on different industries.